Improving Critical Thinking Skills of Class VI Students Building Space Materials through the RME Learning Model - Mariani, Sri; Nurasiah, Iis; Nurmeta, Irda Khaleda (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to describe efforts to improve critical thinking skills in building materials by implementing the learning model of realistic mathematics education (RMEl) at SDN Cijambe Tengah Sukaresmi Village, Cisaat District, Sukabumi Regency for the 2023/2024 academic year in the school year. The research method used is Class Action Research (PTK) with The research design uses the Kelmmis and Mc Taggart model which is carried out in two cycles. Each cycle consists of planning, implementation, action and observation, as well as reflection. Participants in this research are 35 class VI students. This research data collection technique uses a type of test. preltelst and polstelst. The initial research techniques take the form of observation, field notes and documentation. The data analysis technique used is descriptive quantitative. In the pre-cycle, this activity still uses the colonial learning model. Students' mathematical critical thinking skills improve after implementing the RMEl learning model. This can be seen from the learning completion of classically educated students who have experienced an increase. Starting with the pre-cycle where this activity still uses the national learning model, namely 29% or 10 students who completed above the KKM (70) out of a total of 35 students. Then, carrying out the first cycle stage by implementing the RM learning model, the ability to think critically in mathematics resulted in an increase in the total level of 49% or 17 students who completed the KKM, then the research continued with the second cycle stage until they achieved a total completion score of 74% or as many as 26 students who completed the KKM. Therefore, the research was stopped classically because it had reached or exceeded the 70% achievement indicator.This research aims to describe efforts to improve critical thinking skills in building materials by implementing the learning model of realistic mathematics education (RMEl) at SDN Cijambe Tengah Sukaresmi Village, Cisaat District, Sukabumi Regency for the 2023/2024 academic year in the school year. The research method used is Class Action Research (PTK) with The research design uses the Kelmmis and Mc Taggart model which is carried out in two cycles. Each cycle consists of planning, implementation, action and observation, as well as reflection. Participants in this research are 35 class VI students. This research data collection technique uses a type of test. preltelst and polstelst. The initial research techniques take the form of observation, field notes and documentation. The data analysis technique used is descriptive quantitative. In the pre-cycle, this activity still uses the colonial learning model. Students' mathematical critical thinking skills improve after implementing the RMEl learning model. This can be seen from the learning completion of classically educated students who have experienced an increase. Starting with the pre-cycle where this activity still uses the national learning model, namely 29% or 10 students who completed above the KKM (70) out of a total of 35 students. Then, carrying out the first cycle stage by implementing the RM learning model, the ability to think critically in mathematics resulted in an increase in the total level of 49% or 17 students who completed the KKM, then the research continued with the second cycle stage until they achieved a total completion score of 74% or as many as 26 students who completed the KKM. Therefore, the research was stopped classically because it had reached or exceeded the 70% achievement indicator.ellitian    ini    berltujuan    melndelskripsikan    upaya    peningkatan keterampilanberpikirkritismateribangun   ruangdenganpenl  elrapan modl  ellpelmbellajaranrelalistic  mathelmaticselducatioln(RMEldiSDN CijambeTengahDesaSukaresmiKecamatanCisaatKabupatenSukabumi  tahun  pellajaran  2023/2024  diselmelstelr   gelnap.   Meltoldel pelnellitian  yang  digunakanadalahPenl  ellitianTindakan  Kellas(PTK) delngan  delsain  pelnellitian  melnggunakan  modl  ell  Kelmmis  dan  Mc Taggartyangdilakukanselbanyakduasiklus.Seltiapsiklus terldiridari pelrenl  canaan,  pellaksanaan,  tindakan  dan  pelngamatan,  serlta  relflekl  si. PartisipandalampelnellitianiniadalahpelselrtadidikkelasVI selbanyak 35siswa.Telknikpelngumpulandatapenl  ellitianinimelnggunakantels belrupa   pretlelst   dan   polstelst.   Seldangkan   tekl  nik   noln   tesl    belrupa obl  serlvasi,  catatan  lapangan  dan  dolkumelntasi.  Telknik  analisis  data yangdigunakanadalahkuantitatifdelskriptif.Padaprasiklusdimana pada    kegl  iatan    ini    masih    melnggunakan    moldell    pelmbellajaran kolnvelnsiolnal.    Keterampilan    berpikir    kritis    matelmatika    siswa melningkat  setlellah  melnerlapkan  moldell  pelmbellajaran  RMEl.  Hal  ini dapat  dikeltahuidariketluntasanbellajar  pelserlta  didik  secl  ara  klasikal yangmelngalamipelningkatan.Diawalidelnganprasiklusdimanapada kelgiataninimasihmelnggunakanmodl  ellpelmbellajarankolnvelnsiolnal yaituselbeslar29%atau10pelselrtadidikyangtuntas diatasKKM (70) daritoltaljumlahkeslelluruhan35siswa.Kelmudiandilakukantahapan siklusIdenl  ganmelnerlapkanmodl  ellpelmbellajaranRMElkelmampuan berpikirkritismatelmatikamelngalamipelningkatanselbelsar49%atau 17siswa yangtuntasKKM,makapelnellitiantetlapdilanjutkankeltahap siklus  II  sampai  melmpelrollelh  nilai  keltuntasan  selbelsar  74%  atau selbanyak  26  siswa  yang  tuntas  KKM.  Ollelh  selbab  itu,  pelnellitian dihelntikan  selcara   klasikal  karenl  a   tellah   melncapai  atau   mellelbihi indikatorl  ketlerlcapaian70%.xjucThisresearchaimstodescribeeffortstoimprovecriticalthinkingskillsinbuildingmaterialsbyimplementingthelearningmodelofrealisticmathematicseducation(RMEl)atSDNCijambeTengahSukaresmiVillage,CisaatDistrict,SukabumiRegencyforthe2023/2024academicyearintheschoolyear.TheresearchmethodusedisClassActionResearch(PTK)withTheresearchdesignusestheKelmmisandMcTagg